Dynamic Hepatocholescintigraphy with Bromesida® 99mTc - S. P. Mironov; V. B. Sergienko (Вестник рентгенологии и радиологии)
Hepatobiliary scintigraphy using radiopharmaceuticals (RPh) labeled with short-lived technetium‑99m (99mТс) has been used since the mid‑1970s and still retains its diagnostic value. The lecture focuses on key aspects of the pharmacokinetics of lidocaine analogs based on N-substitutions of iminodiacetic acid. The methodology and diagnostic significance of hepatocholescintigraphy with Bromesida® 99mTс (mebrofenin), including computer registration of RPh passage, anatomical and functional characteristics of liver, bile ducts, gallbladder and duodenum, are considered. Scintigraphic semiotics in choledochal cysts, acute and chronic cholecystitis, gallbladder and duodenum dyskinesia, are discussed. The presented clinical case illustrates the possibilities of Bromesida® 99mTс scintigraphy in the gallbladder form anomaly.